Intravascular ultrasound assessment of stent edge restenosis mechanisms and treatment outcomes following percutaneous coronary intervention - Xi Wu; Zhe Liu; Haobo Huang; Mingxing Wu; He Huang; Lei Wang (Scientific Reports)
Abstract This study aimed to elucidate the biological or mechanical causes of stent edge restenosis (SER) via intravascular ultrasound (IVUS). A retrospective assessment was conducted on 126 SER lesions that underwent IVUS prior to revascularization. The primary mechanisms of SER were categorized. (1) neointimal hyperplasia (NIH); (2) neoatherosclerosis; (3) uncovered lesion; (4) stent underexpansion; or (5) a protruding calcified nodule (CN). The predominant biological or mechanical causes of SER were NIH in 42.9% (n = 54) of lesions, neoatherosclerosis in 32.5% (n = 41), uncovered lesion in 14.3% (n = 18), stent underexpansion in 7.9% (n = 10), and protruding CN in 2.4% (n = 3). The 2-year device-oriented clinical endpoints (DoCE) incidence was 7.1% (n = 9). The group with biological causes treated via drug-coated balloons (DCB) exhibited a comparable DoCE rate (9.5%) to those with biological causes treated with drug-eluting stents (DES) and mechanical causes managed with or without restenting (6.0%, HR 2.78, 95% CI: 0.91–9.21; p = 0.161). The majority of the analyzed SERs were attributed to biological causes, including NIH, neoatherosclerosis, and uncovered lesions. The 2-year DoCE rate within patients receiving DCB for mechanically or biologically induced SER was similar to that observed in patients receiving new DES.